An investigation into the neuroprotective properties of melatonin - Southgate, Garrick Steven (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1999)
Until the beginning of this decade the neurohormone, melatonin, had been considered as little more than a tranquillising hormone, responsible for regulating certain circadian and circannual rhythms. In the last eight years, a whole new dimension to melatonin's role in biological organisms has emerged. In 1991 it was discovered [1,2] that melatonin exhibited antioxidant properties. Since then, many researchers [3,4] have found melatonin to be a powerful free radical scavenger and antioxidant. In the present study, the ability of melatonin to offer neuroprotection against glutamate, N-methyl-D-aspartate (NMDA), quinolinic acid (QA) and kainic acid (KA) (collectively referred to as the glutamate receptor agonists) was investigated. It was first shown that stress causes an increase in circulating glucocorticoid concentrations, which resulted in an increase the number of glutamate receptors on synaptic membranes in rat brain homogenate. Melatonin acted to reduce the number of glutamate receptors present on the synaptic membranes, implying that melatonin has neuroprotective properties, as overstimulation of the glutamate receptors leads to excitotoxicity and neurodegeneration. Further investigations showed that the glutamate receptor agonists induce neurodegeneration in primary neuronal cell cultures. Both co-treatment and posttreatment with melatonin against the glutamate receptor agonists, increased neuronal cell viability in a dose dependent manner. Melatonin also appeared to offer protection against quinolinic acid-induced neurodegeneration following intrahippocampal injections of quinolinic acid. The mechanism whereby melatonin offered this protection was investigated. The glutamate receptor agonists caused an increase in intracellular calcium concentrations, which is known [5] to be responsible for initiating the excitotoxic response. Melatonin had no effect on regulating intracellular calcium concentrations Additional studies indicated that melatonin was effective at scavenging superoxide radicals. Production of superoxide radicals was induced by the glutamate receptor agonists in primary neuronal cultures. Superoxide radicals induce lipid peroxidation, which involves the destruction of lipid membranes by chain reactions. By acting as an antioxidant, melatonin was able to reduce quinolinic acid-induced lipid peroxidation in rat brain homogenate, in a dose dependent manner. Melatonin was also effective at reducing lipid peroxidation induced by the glutamate receptor agonists in primary neuronal cultures. Melatonin therefore appeared to be offering neuroprotection by removing superoxide radicals and inhibiting lipid peroxidation. It had been reported [6] that melatonin inhibits nitric oxide synthase activity. This enzyme produces the free radical, nitric oxide, and can also produce superoxide radicals. Melatonin was able to reduce nitric oxide synthase activity in a dose dependent manner. This is a novel method of neuroprotection, as melatonin was now acting as an enzyme regulator. The results obtained demonstrate that melatonin offers neuroprotection against glutamate induced excitotoxicity, by removing free radicals and preventing lipid peroxidation. The neurohormone offers further protection by decreasing the activity of enzymes that aid in the neurotoxic cascade. Melatonin is the most potent naturally occurring free radical scavenger in the body [3]. During aging, the serum concentrations of melatonin decrease [7]. During the senescence of life, free radical damage to the body is at its highest [8], while at the same time melatonin concentrations are at their lowest. Melatonin therefore shows potential for the treatment of diseases and disorders that exhibit an excitotoxic pathology.
Keywords: Melatonin